(untitled) (Journal of Asian Development Studies, 2022)
International migration has played significant role in the development of the recipient households in developing countries. In Azad Kashmir mostly people move to improve their living standard of their households. Due to Remittances health and education of Kashmiri people improved from last many decades. Primary motivation of the study is to check the impact of remittances on the performance of the students in higher education. For this study primary data were collected through questionnaire. Randomly 75 migrants and 75 non-migrants were selected. Ordinary Least Square (OLS) model is used to check the impact of remittances on the Performance of the students. Performance of the students from migrant’s households is less than the students belong to non-migrants’ households. So there is negative relationship between remittances and performance of the students that belongs to migrant’s households. So study concludes that remittances have negative impact on the performance of the students in District Poonch Azad Jammu and Kashmir.